Preparation method of rapid adsorption conductive lithium ion sieve membrane

By introducing PTh@HMO conductive polymer into the lithium-ion sieve membrane and combining ESIX technology, the problems of slow adsorption rate of traditional lithium-ion sieve and easy soluble loss in the regeneration process are solved, and the rapid adsorption and efficient regeneration of lithium ions are achieved, meeting the needs of industrial applications.

CN119500081APending Publication Date: 2025-02-25NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411683661.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional lithium-ion sieves have problems such as slow adsorption rate and easy soluble and damaged regeneration process, which cannot meet industrial needs.

Method used

SP-PDA@PVDF was used as the base film to prepare PTh@HMO conductive polymer and applied it to the ESIX process. A conductive lithium ion sieve membrane (PTh@HMO@SP-PDA@PVDF) was developed to improve adsorption rate and cycling stability.

Benefits of technology

It realizes rapid adsorption and efficient regeneration of lithium ions, reduces manganese dissolution, improves the conductive properties and cycle stability of the material, and meets the needs of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500081A_ABST
    Figure CN119500081A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a rapid adsorption conductive lithium ion sieve membrane, and relates to the field of preparation of lithium ion sieve membranes. The invention aims to solve the problems that the traditional lithium ion sieve is too slow in adsorption rate, easy to dissolve and damage in the regeneration process and incapable of meeting industrial requirements. According to the invention, SP-PDA-coated PVDF is used as a base membrane to prepare a PTH-coated HMO conductive polymer, and the PTH-coated HMO conductive polymer is applied to an ESIX process to develop a conductive lithium ion sieve membrane which is good in conductivity, low in manganese dissolution loss and capable of rapidly adsorbing. The method comprises the following steps: 1, preparing an SP-PDA coated PVDF membrane; 2, preparing a PTH-HMO conductive polymer; and 3, preparing the PTH-HMO-SP-PDA-PVDF conductive polymer. The prepared rapid adsorption conductive lithium ion sieve membrane has longer service life, and the replacement frequency and the maintenance cost are reduced. According to the invention, the rapid adsorption conductive lithium ion sieve membrane can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparing lithium ion sieve membranes, and in particular to a method for preparing a fast adsorption conductive lithium ion sieve membrane. Background Art

[0002] At present, the main technologies for extracting lithium from brine include precipitation, solvent extraction, ion exchange adsorption and ion sieve adsorption. Among them, the lithium ion sieve adsorption method has a large adsorption capacity, good recyclability and high selectivity, so the lithium ion sieve lithium extraction technology is considered to be the lithium extraction technology with the greatest industrial potential. However, the ion sieve itself is in powder form and is easy to agglomerate during the adsorption process, resulting in a decrease in adsorption capacity and a significant decrease in adsorption rate. The dissolution loss during the regeneration process is serious, which is not conducive to industrial lithium extraction production. In order to solve the above problems, granulation and film formation are often used, but the adsorption rate is still slow.

[0003] As an environmentally friendly ion separation method, electrochemical switch ion exchange (ESIX) technology has attracted extensive attention in the separation and recovery of various ions. This method achieves reversible uptake and release of target ions by changing the redox state of the electroactive ion exchange material (EIXM) deposited on the electrode, and the regeneration of EXIM can be easily achieved by driving the reverse ion exchange with electrical energy alone, reducing the lithium ion sieve loss caused by the conventional regeneration process.

[0004] Therefore, traditional lithium ion sieves have the problems of slow adsorption rate and easy dissolution during the regeneration process, which cannot meet industrial needs. It is necessary to develop a fast-adsorbing conductive lithium ion sieve membrane to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of slow adsorption rate, easy dissolution during regeneration and inability to meet industrial needs of traditional lithium ion sieves, and to provide a method for preparing a fast adsorption conductive lithium ion sieve membrane.

[0006] The present invention uses SP-PDA@PVDF as a base membrane to prepare PTh@HMO conductive polymer, and applies it to the ESIX process to develop a conductive lithium ion sieve membrane (PTh@HMO@SP-PDA@PVDF) with good conductivity, low manganese dissolution loss and rapid adsorption.

[0007] A method for preparing a fast adsorption conductive lithium ion sieve membrane is specifically completed by the following steps:

[0008] 1. Preparation of SP-PDA@PVDF membrane:

[0009] ①, mix the sodium acetate buffer solution and dopamine hydrochloride evenly, then add sodium periodate solution dropwise, mix evenly, and obtain mixed solution I;

[0010] ②. Make one surface of the PVDF membrane contact with the mixed solution I, and the other surface contact with the air. Keep this state and oscillate the mixed solution I at a constant temperature for a period of time, and one surface of the PVDF membrane is modified;

[0011] ③. One unmodified surface of the PVDF membrane was contacted with the mixed solution I, and the other surface was contacted with air. The mixed solution I was kept in this state and oscillated at a constant temperature for a period of time. Then, the two surfaces of the PVDF membrane were washed with deionized water, and finally dried to obtain the SP-PDA@PVDF membrane;

[0012] 2. Preparation of PTh@HMO conductive polymer:

[0013] ①, Grind LiOH·H2O and MnO2 in an agate mortar, transfer to a corundum crucible after mixing evenly, and then put it into a muffle furnace, heat it to the calcination temperature and calcine for a period of time to obtain a precursor; Use HCl solution to pickle the precursor for a period of time, then filter and wash it with deionized water, and finally dry it to obtain an ion sieve;

[0014] ②, add the ion sieve to tetrahydrofuran, ultrasonicate for a period of time, then add thiophene and anhydrous FeCl3, ultrasonicate for a period of time, then use an ice bath to control the reaction temperature and stir at low temperature for a period of time, filter, and then wash and dry the obtained solid product to obtain PTh@HMO conductive polymer;

[0015] 3. Preparation of PTh@HMO@SP-PDA@PVDF conductive polymer:

[0016] PTh@HMO conductive polymer is added to anhydrous methanol and ultrasonically mixed for a period of time to obtain mixed solution II; SP-PDA@PVDF membrane is immersed in mixed solution II, then heated to 65°C, condensed and refluxed under stirring conditions for a period of time, and then the membrane is taken out and washed with deionized water to remove excess polymer on the surface, and dried to obtain PTh@HMO@SP-PDA@PVDF, which is a fast adsorption conductive lithium ion sieve membrane.

[0017] Principle of the present invention:

[0018] 1. The present invention controls the ion exchange process so that the ions can overcome resistance and transfer in a directional manner, thereby accelerating the adsorption rate of the target ions; polythiophene (PTh), as a conductive material with high conductivity, can improve the conductivity of the ion sieve and accelerate the transmission speed of ions in the screening process, thereby improving the screening efficiency; PTh is used to coat HMO to prepare PTh@HMO ion exchange material for the ESIX process, which greatly accelerates the adsorption rate of lithium ions and is more in line with the needs of industrial applications;

[0019] Second, the present invention combines the PTh-coated ion sieve with the modified SP-PDA@PVDF base film to form a three-dimensional network structure, increase the specific surface area, and provide more attachment sites for the ion sieve; the surface coating PTh is formed by chemical oxidation, which not only improves the structural stability and conductivity of the material, but also forms a physical barrier, reduces the direct contact between the active material in the electrode and the electrolyte, and protects the low-valent Mn 3+ , inhibiting the disproportionation reaction; the conductive lithium ion sieve membrane combined with ESIX technology controls the ion exchange process, allowing the ions to overcome resistance and transfer in a directional manner, thereby increasing the amount and rate of lithium adsorption, and at the same time significantly improving the cycle stability.

[0020] Advantages of the present invention:

[0021] 1. Polythiophene (PTh) with good electrical conductivity is used as a surface coating to coat the ion sieve (HMO), which reduces the manganese dissolution problem and increases the adsorption rate of lithium ions;

[0022] Second, the PTh@HMO ion exchange material was prepared for the ESIX process, which greatly accelerated the adsorption rate of lithium ions and better met the needs of industrial applications;

[0023] Third, by loading conductive polymers on the SP-PDA@PVDF membrane, dual integration of conduction and adsorption was achieved;

[0024] 4. Compared with other ion exchange materials, conductive lithium ion sieve membranes usually have a longer service life, reducing replacement frequency and maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of PTh@HMO@SP-PDA@PVDF prepared in Example 1; Figure 1 a is HMO, b is PTh@HMO, c is the initial PVDF membrane, d is SP-PDA@PVDF membrane, e is PTh@HMO@SP-PDA@PVDF, and f is the EDS element mapping of the distribution of C, N, O, and Mn on the PTh@HMO@SP-PDA@PVDF membrane;

[0026] Figure 2 The PTh@HMO@SP-PDA@PVDF prepared in Example 1 has a strong affinity for Li in the presence of competitive metal ions. + Adsorption selectivity;

[0027] Figure 3 is the relationship between the number of cycle desorption and the adsorption capacity of PTh@HMO@SP-PDA@PVDF prepared in Example 1;

[0028] Figure 4It is the effect of different pH values ​​on the adsorption performance of PTh@HMO@SP-PDA@PVDF prepared in Example 1;

[0029] Figure 5 This is the relationship between the adsorption time and adsorption capacity of PTh@HMO@SP-PDA@PVDF prepared in Example 1. DETAILED DESCRIPTION

[0030] Specific implementation method 1: This implementation method is a method for preparing a fast adsorption conductive lithium ion sieve membrane, which is specifically completed according to the following steps:

[0031] 1. Preparation of SP-PDA@PVDF membrane:

[0032] ①, mix the sodium acetate buffer solution and dopamine hydrochloride evenly, then add sodium periodate solution dropwise, mix evenly, and obtain mixed solution I;

[0033] ②. Make one surface of the PVDF membrane contact with the mixed solution I, and the other surface contact with the air. Keep this state and oscillate the mixed solution I at a constant temperature for a period of time, and one surface of the PVDF membrane is modified;

[0034] ③. One unmodified surface of the PVDF membrane was contacted with the mixed solution I, and the other surface was contacted with air. The mixed solution I was kept in this state and oscillated at a constant temperature for a period of time. Then, the two surfaces of the PVDF membrane were washed with deionized water, and finally dried to obtain the SP-PDA@PVDF membrane;

[0035] 2. Preparation of PTh@HMO conductive polymer:

[0036] ①, Grind LiOH·H2O and MnO2 in an agate mortar, transfer to a corundum crucible after mixing evenly, and then put it into a muffle furnace, heat it to the calcination temperature and calcine for a period of time to obtain a precursor; Use HCl solution to pickle the precursor for a period of time, then filter and wash it with deionized water, and finally dry it to obtain an ion sieve;

[0037] ②, add the ion sieve to tetrahydrofuran, ultrasonicate for a period of time, then add thiophene and anhydrous FeCl3, ultrasonicate for a period of time, then use an ice bath to control the reaction temperature and stir at low temperature for a period of time, filter, and then wash and dry the obtained solid product to obtain PTh@HMO conductive polymer;

[0038] 3. Preparation of PTh@HMO@SP-PDA@PVDF conductive polymer:

[0039] PTh@HMO conductive polymer is added to anhydrous methanol and ultrasonically mixed for a period of time to obtain mixed solution II; SP-PDA@PVDF membrane is immersed in mixed solution II, then heated to 65°C, condensed and refluxed under stirring conditions for a period of time, and then the membrane is taken out and washed with deionized water to remove excess polymer on the surface, and dried to obtain PTh@HMO@SP-PDA@PVDF, which is a fast adsorption conductive lithium ion sieve membrane.

[0040] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the concentration of the sodium acetate buffer solution in step 1① is 50mmol / L, pH=5.0; the concentration of the sodium periodate solution in step 1① is 15mmol / L to 25mmol / L. The other steps are the same as those in specific embodiment 1.

[0041] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the mass volume ratio of dopamine hydrochloride, sodium acetate buffer solution and sodium periodate solution described in step 1① is (0.1g-0.3g):80mL:20mL. The other steps are the same as specific embodiment 1 or 2.

[0042] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that the temperature of the constant temperature oscillation described in step 1② and step 1③ is 25°C, and the oscillation speed is 130r·min -1 ~140r·min -1 , the oscillation time is 5h to 7h; in step 1③, the two surfaces of the PVDF membrane are washed 3 to 5 times with deionized water, and finally dried at 50℃ to 70℃ for 0.5h to 1h. The other steps are the same as those in specific embodiments 1 to 3.

[0043] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the mass ratio of LiOH·H2O and MnO2 described in step 2① is (0.5-0.8):(1-2); the heating rate described in step 2① is 5℃min -1 ~10℃min -1 The calcination temperature is 500°C to 600°C, and the calcination time is 5h to 7h. The other steps are the same as those in the first to fourth embodiments.

[0044] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the concentration used in step 2① is 1 mol·L -1 The precursor is acid-washed with HCl solution for 5h to 7h at a washing temperature of 25°C, then filtered and washed 2 to 3 times with deionized water, and finally dried at 50°C to 70°C for 1h to 2h. The other steps are the same as those in the first to fifth embodiments.

[0045] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is (0.4g~0.6g):(4g~5g):(0.6mL~1mL):(45mL~55mL); the ultrasonic time described in step 2② is 5min~15min. The other steps are the same as those of specific embodiments 1 to 6.

[0046] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the temperature of the low-temperature stirring reaction described in step two ② is 5°C to 10°C, and the time is 7h to 8h; in step two ②, the solid product obtained is washed 2 to 4 times with 1 mol / L hydrochloric acid, methanol and deionized water respectively, and then dried at 70°C to 90°C for 4h to 6h. The other steps are the same as those of specific embodiments one to seven.

[0047] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the volume ratio of the mass of the PTh@HMO conductive polymer described in step 3 to anhydrous methanol is 0.5 g: (120 mL to 140 mL); the ultrasonic mixing time described in step 3 is 3 min to 5 min. The other steps are the same as those of specific embodiments 1 to 8.

[0048] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the condensation reflux time in step 3 is 8h to 9h, and the stirring speed during condensation reflux is 30r·min -1 ~50r·min -1 The drying temperature in step 3 is 50°C to 70°C, and the drying time is 0.5h to 1h. The other steps are the same as those in specific embodiments 1 to 9.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1: A method for preparing a fast adsorption conductive lithium ion sieve membrane is specifically completed according to the following steps:

[0051] 1. Preparation of SP-PDA@PVDF membrane:

[0052] ①, mix the sodium acetate buffer solution and dopamine hydrochloride evenly, then add sodium periodate solution dropwise, mix evenly, and obtain mixed solution I;

[0053] The concentration of the sodium acetate buffer solution described in step 1① is 50mmol / L, pH=5.0;

[0054] The concentration of the sodium periodate solution described in step 1① is 20mmol / L;

[0055] The mass volume ratio of dopamine hydrochloride, sodium acetate buffer solution and sodium periodate solution described in step 1① is 0.2g:80mL:20mL;

[0056] ②. One surface of the PVDF membrane (thickness 0.45 μm, diameter 47 mm) was contacted with the mixed solution I, and the other surface was contacted with air. The mixed solution I was kept in this state and oscillated at a constant temperature for a period of time, and one surface of the PVDF membrane was modified;

[0057] ③. One unmodified surface of the PVDF membrane was contacted with the mixed solution I, and the other surface was contacted with air. The mixed solution I was kept in this state and oscillated at a constant temperature for a period of time. Then, the two surfaces of the PVDF membrane were washed with deionized water, and finally dried to obtain the SP-PDA@PVDF membrane;

[0058] The temperature of the constant temperature oscillation in step 1② and step 1③ is 25°C, and the oscillation speed is 130r·min -1 , the oscillation time is 6h;

[0059] In step 1③, the two surfaces of the PVDF membrane were washed three times with deionized water, and finally dried at 60°C for 0.5h;

[0060] 2. Preparation of PTh@HMO conductive polymer:

[0061] ①, LiOH·H2O and MnO2 are ground in an agate mortar, mixed evenly and transferred to a corundum crucible, then placed in a muffle furnace, heated to the calcination temperature and calcined for a period of time to obtain a precursor; the precursor is acidified with HCl solution for a period of time, then filtered and washed with deionized water, and finally dried to obtain an ion sieve (HMO);

[0062] The mass ratio of LiOH·H2O and MnO2 described in step 2① is 0.8:1;

[0063] The heating rate described in step 2① is 5℃min -1 ; The calcination temperature is 550°C; the calcination time is 6h;

[0064] The concentration used in step 2① is 1 mol·L -1 The precursor was acid-washed with HCl solution for 6 h at a temperature of 25 °C, then filtered and washed with deionized water for 3 times, and finally dried at 60 °C for 1 h;

[0065] ②, add the ion sieve to tetrahydrofuran, ultrasonicate for 15 minutes, then add thiophene and anhydrous FeCl3, ultrasonicate for 5 minutes, then use an ice bath to control the reaction temperature and stir at low temperature for a period of time, filter, wash and dry the obtained solid product to obtain PTh@HMO conductive polymer;

[0066] The mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.5g

[0067] :4.63g:0.8mL:50mL;

[0068] The temperature of the low temperature stirring reaction in step 2② is 8°C and the time is 8h;

[0069] In step 2②, the solid product obtained is washed three times with 1 mol / L hydrochloric acid, methanol and deionized water respectively, and then dried at 80°C for 5 hours;

[0070] 3. Preparation of PTh@HMO@SP-PDA@PVDF conductive polymer:

[0071] PTh@HMO conductive polymer was added to anhydrous methanol and ultrasonically mixed for 5 minutes to obtain mixed solution II; SP-PDA@PVDF membrane was immersed in mixed solution II, and then heated to 65°C, condensed and refluxed for a period of time under stirring conditions, and then the membrane was taken out and washed with deionized water to remove excess polymer on the surface, and dried to obtain PTh@HMO@SP-PDA@PVDF, which is a fast adsorption conductive lithium ion sieve membrane;

[0072] The mass ratio of the PTh@HMO conductive polymer described in step 3 to the volume ratio of anhydrous methanol is 0.5 g:130 mL;

[0073] The condensation reflux time in step 3 is 9 hours, and the stirring speed during condensation reflux is 30 r·min -1 ;

[0074] The drying temperature in step 3 is 60° C. and the drying time is 1 h.

[0075] Example 2: The difference between this example and example 1 is that the temperature of the constant temperature oscillation in step 1② and step 1③ is 25°C, and the oscillation speed is 130 r·min -1 , the oscillation time is 4h. Other steps and parameters are the same as those in Example 1. Compared with Example 1, the lithium ion adsorption amount of Example 2 reaches 43.6mg / g, which is slightly lower than that of Example 1.

[0076] Example 3: The difference between this example and example 1 is that the temperature of the constant temperature oscillation in step 1② and step 1③ is 25°C, and the oscillation speed is 130 r·min -1 , the oscillation time is 5h. Other steps and parameters are the same as those in Example 1. Compared with Example 1, the lithium ion adsorption capacity of Example 3 reaches 50.9mg / g.

[0077] Example 4: The difference between this example and Example 1 is that the temperature of the constant temperature oscillation in step 1② and step 1③ is 25°C, and the oscillation speed is 130r·min -1 , the oscillation time is 7h. The other steps and parameters are the same as those in Example 1. Compared with Example 1, Example 4 has the longest modification time and the highest surface modification degree, and the lithium ion adsorption capacity is no longer increased, which is 56.3 mg / g.

[0078] Example 5: The difference between this example and Example 1 is that the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.1g:4.63g:0.8mL:50mL. The other steps and parameters are the same as those in Example 1. Compared with Example 1, Example 5 has a lower amount of ion sieve added and fewer active sites, and the lithium ion adsorption amount is lower, reaching 43.2mg / g.

[0079] Example 6: The difference between this example and Example 1 is that the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.2g:4.63g:0.8mL:50mL. The other steps and parameters are the same as those in Example 1. Compared with Example 1, the amount of ion sieve added in Example 6 is increased, the active sites are also increased, and the adsorption amount is improved to 47.8mg / g.

[0080] Example 7: The difference between this example and Example 1 is that the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.3g:4.63g:0.8mL:50mL. The other steps and parameters are the same as those in Example 1. Compared with Example 1, Example 7 further increases the amount of ion sieve added, and the adsorption amount is further increased to 51.4mg / g.

[0081] Example 8: The difference between this example and Example 1 is that the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.4g:4.63g:0.8mL:50mL. The other steps and parameters are the same as those in Example 1. Compared with Example 1, the adsorption amount of Example 8 reaches 52.9mg / g.

[0082] Example 9: The difference between this example and Example 1 is that the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.4g:4.63g:0.4mL:50mL. The other steps and parameters are the same as those in Example 1. Compared with Example 1, the less thiophene addition in Example 9 leads to a thinner PTh layer, thus providing fewer active sites, so the lithium ion adsorption amount reaches 50.8mg / g, which is slightly lower than that in Example 1.

[0083] Example 10: The difference between this example and Example 1 is that the mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is 0.4g:4.63g:0.6mL:50mL. The other steps and parameters are the same as those in Example 1. Compared with Example 1, the amount of thiophene added in Example 10 will form a moderate PTh layer, and the adsorption amount reaches 51.5mg / g, which is slightly lower than that in Example 1.

[0084] Figure 1 is a scanning electron microscope image of PTh@HMO@SP-PDA@PVDF prepared in Example 1; Figure 1 a is HMO, b is PTh@HMO, c is the initial PVDF membrane, d is SP-PDA@PVDF membrane, e is PTh@HMO@SP-PDA@PVDF, and f is the EDS element mapping of the distribution of C, N, O, and Mn on the PTh@HMO@SP-PDA@PVDF membrane;

[0085] from Figure 1 It can be seen that: the ion sieve is composed of small crystalline particles, some of which are spinel-shaped; PTh@HMO retains its crystal shape well; the surface of the PVDF membrane is relatively smooth and has a typical macroporous structure; the relatively rough surface of the SP-PDA@PVDF membrane indicates that the SP-PDA layer is successfully grafted onto the PVDF base membrane; after membrane loading, PTh is evenly distributed on the surface of the HMO particles, making the particle shape more regular; these changes are conducive to improving the conductivity of the material and accelerating the directional migration of ions in the membrane. The corresponding element mapping shows that C, N, O, and Mn are evenly distributed, further confirming the successful preparation of the material.

[0086] PTh@HMO@SP-PDA@PVDF was cut into a 1×1 cm shape, and the ion sieve membrane was pasted on the cut titanium sheet using conductive silver glue to obtain an electrode sheet. + Mg 2+ 、Na + and K + The adsorption of PTh@HMO@SP-PDA@PVDF on Li +The adsorption selectivity of Li + Mg 2+ 、Na + and K + Adsorption capacity on lithium ion sieve membrane. Figure 2 As shown;

[0087] Figure 2 The PTh@HMO@SP-PDA@PVDF prepared in Example 1 has a strong affinity for Li in the presence of competitive metal ions. + Adsorption selectivity;

[0088] from Figure 2 It can be seen that the PTh@HMO@SP-PDA@PVDF prepared in Example 1 has a good + The adsorption capacity is much higher than that of the competing ion Mg 2+ 、Na + and K + In the presence of competing ions, PTh@HMO@SP-PDA@PVDF can effectively absorb Li + The adsorption capacity can still reach 53.6 mg / g. This indicates that in the presence of Mg 2+ 、Na 2+ and K + Under the condition of interference, PTh@HMO@SP-PDA@PVDF effectively and selectively adsorbed Li + .

[0089] In order to determine the cyclic stability of the lithium ion sieve membrane, 10 cyclic adsorption and desorption experiments were carried out to test its stability. Figure 3 As shown;

[0090] Figure 3 is the relationship between the number of cycle desorption and the adsorption capacity of PTh@HMO@SP-PDA@PVDF prepared in Example 1;

[0091] PTh@HMO@SP-PDA@PVDF for Li + The adsorption capacity of PTh@HMO@SP-PDA@PVDF decreased slightly, but basically showed a stable trend. This is because PTh coated HMO helps to protect the internal structure of the ion sieve and reduce the problem of manganese dissolution. At the same time, the lithium ion sieve is combined with the membrane material. Because the membrane material has good mechanical properties, the conductive lithium ion sieve membrane still maintains its chemical stability after 10 cycles of desorption, extending its service life. The experimental results show that even after 10 cycles of adsorption and desorption, the adsorption amount of PTh@HMO@SP-PDA@PVDF has not decreased much (from 53.6 mg / g to 50.2 mg / g), proving that the conductive lithium ion sieve membrane is a stable material that is very suitable for continuous operation and industrial applications.

[0092] The pH value of the solution is a key parameter affecting the adsorption capacity of the adsorbent, such as Figure 4 As shown; Figure 4 It is the effect of different pH values ​​on the adsorption performance of PTh@HMO@SP-PDA@PVDF prepared in Example 1;

[0093] Figure 4 It is the effect of different pH values ​​on the adsorption performance of PTh@HMO@SP-PDA@PVDF prepared in Example 1;

[0094] Depend on Figure 4 It can be seen that the adsorption amount increases slowly with the increase of pH value, indicating that the increase of pH value is conducive to adsorption. + The resistance to entering the ion sieve becomes larger and the adsorption capacity is smaller; when the pH value is higher, H + Easy to be Li + Replace with OH - reaction.

[0095] The new conductive lithium ion sieve membrane is used in the ESIX process, and rapid adsorption is carried out under the action of electric field force. Figure 5 As shown;

[0096] Figure 5 is the relationship between the adsorption time and adsorption capacity of PTh@HMO@SP-PDA@PVDF prepared in Example 1;

[0097] Figure 5 This is the relationship between adsorption time and adsorption capacity. In 0-10min, the adsorption rate accelerates, and starts to change slowly in 10-20min, and gradually reaches equilibrium within 30min. It can be seen from the figure that in the initial stage of adsorption, the adsorption rate is large and the adsorption capacity rises rapidly, indicating that the lithium adsorption rate of the lithium ion sieve membrane is fast at the beginning. As time goes by, the concentration of lithium ions in the solution decreases, and the adsorption rate gradually decreases. After 30min, the adsorption amount basically does not increase, and the adsorption gradually reaches saturation.

Claims

1. A method for preparing a fast adsorption conductive lithium ion sieve membrane, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of SP-PDA@PVDF membrane: ①, mix the sodium acetate buffer solution and dopamine hydrochloride evenly, then add sodium periodate solution dropwise, mix evenly, and obtain mixed solution I; ②. Make one surface of the PVDF membrane contact with the mixed solution I, and the other surface contact with the air. Keep this state and oscillate the mixed solution I at a constant temperature for a period of time, and one surface of the PVDF membrane is modified; ③. One unmodified surface of the PVDF membrane was contacted with the mixed solution I, and the other surface was contacted with air. The mixed solution I was kept in this state and oscillated at a constant temperature for a period of time. Then, the two surfaces of the PVDF membrane were washed with deionized water, and finally dried to obtain the SP-PDA@PVDF membrane; 2. Preparation of PTh@HMO conductive polymer: ①, Grind LiOH·H2O and MnO2 in an agate mortar, transfer to a corundum crucible after mixing evenly, and then put it into a muffle furnace, heat it to the calcination temperature and calcine for a period of time to obtain a precursor; Use HCl solution to pickle the precursor for a period of time, then filter and wash it with deionized water, and finally dry it to obtain an ion sieve; ②, add the ion sieve to tetrahydrofuran, ultrasonicate for a period of time, then add thiophene and anhydrous FeCl3, ultrasonicate for a period of time, then use an ice bath to control the reaction temperature and stir at low temperature for a period of time, filter, and then wash and dry the obtained solid product to obtain PTh@HMO conductive polymer; 3. Preparation of PTh@HMO@SP-PDA@PVDF conductive polymer: PTh@HMO conductive polymer is added to anhydrous methanol and ultrasonically mixed for a period of time to obtain mixed solution II; SP-PDA@PVDF membrane is immersed in mixed solution II, then heated to 65°C, condensed and refluxed under stirring conditions for a period of time, and then the membrane is taken out and washed with deionized water to remove excess polymer on the surface, and dried to obtain PTh@HMO@SP-PDA@PVDF, which is a fast adsorption conductive lithium ion sieve membrane.

2. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The concentration of the sodium acetate buffer solution described in step 1① is 50mmol / L, pH=5.0; the concentration of the sodium periodate solution described in step 1① is 15mmol / L~25mmol / L.

3. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The mass volume ratio of dopamine hydrochloride, sodium acetate buffer solution and sodium periodate solution described in step 1① is (0.1g~0.3g):80mL:20mL.

4. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The temperature of the constant temperature oscillation in step 1② and step 1③ is 25°C, and the oscillation speed is 130r·min -1 ~140r·min -1 , the oscillation time is 5h~7h; in step 1③, the two surfaces of the PVDF membrane are washed 3~5 times with deionized water, and finally dried at 50℃~70℃ for 0.5h~1h.

5. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The mass ratio of LiOH·H2O and MnO2 in step 2① is (0.5-0.8):(1-2); the heating rate in step 2① is 5℃min -1 ~10℃min -1 ; The calcination temperature is 500℃~600℃; The calcination time is 5h~7h.

6. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The concentration used in step 2① is 1 mol·L -1 The precursor is acid-washed with HCl solution for 5h to 7h at a cleaning temperature of 25°C, then filtered and washed 2 to 3 times with deionized water, and finally dried at 50°C to 70°C for 1h to 2h.

7. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The mass volume ratio of the ion sieve, anhydrous FeCl3, thiophene and tetrahydrofuran described in step 2② is (0.4g~0.6g):(4g~5g):(0.6mL~1mL):(45mL~55mL); the ultrasonic time described in step 2② is 5min~15min.

8. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The temperature of the low-temperature stirring reaction described in step 2② is 5°C~10°C, and the time is 7h~8h; in step 2②, the solid product obtained is washed 2 to 4 times with 1 mol / L hydrochloric acid, methanol and deionized water respectively, and then dried at 70°C~90°C for 4h~6h.

9. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The volume ratio of the mass of the PTh@HMO conductive polymer described in step 3 to anhydrous methanol is 0.5 g:(120 mL to 140 mL); the time of ultrasonic mixing described in step 3 is 3 min to 5 min.

10. The method for preparing a fast adsorption conductive lithium ion sieve membrane according to claim 1, characterized in that The condensation reflux time in step 3 is 8h to 9h, and the stirring speed during condensation reflux is 30r / min -1 ~50r·min -1 The drying temperature in step 3 is 50°C to 70°C, and the drying time is 0.5h to 1h.

Citation Information

Cited By

  • Hybrid membrane capable of selectively transmitting lithium ions as well as preparation method and application of hybrid membrane

    CN119909547A